2016
DOI: 10.1111/gec3.12255
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Urban Regeneration? Resourcing Critical Generative Accounts of Urban Regeneration through Assemblage.

Abstract: In critical urban studies, managed urban regeneration has been linked to trajectories of neo-liberalising urban policy and urban entrepreneurialism. While the insights arising from this work have been many and valuable, significant gaps remain particularly in terms of the foci of analysis and the conception of politics. In this paper, we aim to address these gaps and to reposition the conceptualization of regeneration as a performed and emergent consequence of 'relatedness' and as subject to a range of relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Money from corporate development in Woolwich largely financed the recent redesign of the case study site. We suggest that while critical urban studies have correctly revealed the destructive and unjust effects of neoliberal urbanism (Peck et al., ) especially as austerity policies intensified (Peck, ), possible temporary advantages of certain aspects of urban regeneration to existing residents have been missed (McGuirk et al, ), exemplifying a disjuncture between overarching, rhetorical metanarratives and more grounded experiences of change (Linebaugh, ).…”
Section: Introductionmentioning
confidence: 92%
“…Money from corporate development in Woolwich largely financed the recent redesign of the case study site. We suggest that while critical urban studies have correctly revealed the destructive and unjust effects of neoliberal urbanism (Peck et al., ) especially as austerity policies intensified (Peck, ), possible temporary advantages of certain aspects of urban regeneration to existing residents have been missed (McGuirk et al, ), exemplifying a disjuncture between overarching, rhetorical metanarratives and more grounded experiences of change (Linebaugh, ).…”
Section: Introductionmentioning
confidence: 92%
“…Assemblage urbanism provides important resources for expanding urban political geography to consider the generative capacity of linked socio-material systems (McFarlane, 2008). It has done much to render more visible the diverse actors, technologies, and materials drawn into uncertain urban processes (McGuirk et al, 2016). Yet, it is the ontological malleability of the material, rather than the diversity of elements per se, that Deleuze and Guattari (1987) draw our attention to.…”
Section: Assemblage and Ontological Diversitymentioning
confidence: 99%
“…While assemblage thinking thus neglected social macro levels and focused on local levels instead--for example, urban development and its logic (see McGuirk et al, 2016)--it nevertheless did not advance much into the details of social and material practices. For instance, the level of individual neighbourhoods has been addressed only reluctantly.…”
Section: The Concept Of Assemblage: Imagining Urban Practicesmentioning
confidence: 99%